Action Plan on Base Erosion and Profit Shifting (Russian version). - OECD. (Paris : OECD Publishing, 2014)
This action plan, created in response to a request by the G20, identifies a set of domestic and international actions to address the problems of base erosion and profit sharing.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books